Panoptic clinical review of the current and future treatment of relapsed/refractory T-cell lymphomas: Peripheral T-cell lymphomas. (March 2016) - Zinzani, Pier Luigi; Bonthapally, Vijayveer; Huebner, Dirk; Lutes, Richard; Chi, Andy; Pileri, Stefano
Highlights: About 70% of patients with PTCLs develop relapsed/refractory disease. Four drugs are specifically approved for use in this setting. Response rates with pralatrexate, romidepsin, and belinostat range from 25 to 54%. Brentuximab vedotin achieves responses in 86% of sALCL patients. Other novel targeted therapies and combinations are showing great promise. Abstract: Peripheral T-cell lymphomas (PTCLs) tend to be aggressive and chemorefractory, with about 70% of patients developing relapsed/refractory disease. Prior to 2009, chemotherapies were the only options for relapsed/refractory PTCL, other than hematopoietic transplants. However, chemotherapy only improves survival by about 1 month compared with palliation. Four drugs are now approved in the US to treat relapsed/refractory PTCL: pralatrexate, romidepsin, belinostat, and brentuximab vedotin (for systemic anaplastic large cell lymphoma [sALCL]). Response rates with pralatrexate, romidepsin, and belinostat range from 25 to 54% in mixed relapsed/refractory PTCL populations, while 86% of sALCL patients respond to brentuximab vedotin. Here, we critically evaluate the evidence supporting the current drug treatment of relapsed/refractory PTCL, and look to the future to see how the treatment panorama may change with the advent of new targeted therapies, some of which (e.g., alisertib in PTCL and mogamulizumab in CCR4-positive adult T-cell leukemia/lymphoma) are already in phase 3 trials.